2016
DOI: 10.1126/scisignal.aaf3273
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 3 supports endochondral bone formation by controlling cytokine signaling and matrix remodeling

Abstract: Histone deacetylase (HDAC) inhibitors are efficacious epigenetic-based therapies for some cancers and neurological disorders; however, each of these drugs inhibits multiple HDACs and has detrimental effects on the skeleton. To better understand how HDAC inhibitors affect endochondral bone formation, we conditionally deleted one of their targets, Hdac3, pre- and postnatally in type II collagen α1 (Col2α1)–expressing chondrocytes. Embryonic deletion was lethal, but postnatal deletion of Hdac3 delayed secondary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
87
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 65 publications
(98 citation statements)
references
References 94 publications
10
87
1
Order By: Relevance
“…We previously demonstrated Hdac3 is expressed during skeletal development, as early as E14.5 and continues to be robustly expressed by growth plate chondrocytes into adulthood (34, 52, 53). Tissue-specific deletion of Hdac3 in chondrocytes with tamoxifen-inducible type II collagen alpha 1 Cre (Col2a1ERT-Cre) caused dramatic delays in endochondral ossification (34, 53).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously demonstrated Hdac3 is expressed during skeletal development, as early as E14.5 and continues to be robustly expressed by growth plate chondrocytes into adulthood (34, 52, 53). Tissue-specific deletion of Hdac3 in chondrocytes with tamoxifen-inducible type II collagen alpha 1 Cre (Col2a1ERT-Cre) caused dramatic delays in endochondral ossification (34, 53).…”
Section: Resultsmentioning
confidence: 99%
“…Tissue-specific deletion of Hdac3 in chondrocytes with tamoxifen-inducible type II collagen alpha 1 Cre (Col2a1ERT-Cre) caused dramatic delays in endochondral ossification (34, 53). Genome-wide transcriptional profiling of Hdac3-depleted chondrocytes showed that markers of chondrocyte maturation, extracellular matrix, and bone development were suppressed with Hdac3-deficiency, while cartilage catabolic genes, like matrix metalloproteinases (e.g., Mmp13) were highly induced (53). To understand these Hdac3-dependent changes in matrix degrading enzymes, immature murine chondrocytes (IMCs) were isolated from 1-week-old Hdac3 fl/fl mice, plated in micromasses, and transduced with Ad-GFP or Ad-Cre to generate control and Hdac3-deficient IMCs, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations